2014
DOI: 10.1002/jmv.23898
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug resistance among antiretroviral‐naïve and treatment experienced patients infected with HIV in Iran

Abstract: Resistance to antiretroviral therapy (ART) threatens the success of programs to reduce HIV morbidity and mortality, particularly in countries with few treatment options. In the present study, genotype and phenotype data from ART-naïve and experienced hospitalized patients infected with HIV in Tehran, Iran were used to assess the prevalence and types of transmitted (TDR) and acquired drug resistance (ADR) mutations. All 30 participants naïve to ART and 62 of 70 (88.6%) participants receiving ART had detectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
8
19
2
Order By: Relevance
“…HIV genome was isolated from patients who were receiving HARRT under the supervision of behavioral medicine clinic (Immam khomeini hospital Tehran-Iran). In agreement with previous studies in Iran, most of the patients receiving antiretroviral therapy with the detectable virus had evidence of drug resistance mutation [13]. Many of patients were resistance to multiple drug classes and many of these mutations elaborate resistancy to other drugs in the same class.…”
Section: Discussionsupporting
confidence: 90%
“…HIV genome was isolated from patients who were receiving HARRT under the supervision of behavioral medicine clinic (Immam khomeini hospital Tehran-Iran). In agreement with previous studies in Iran, most of the patients receiving antiretroviral therapy with the detectable virus had evidence of drug resistance mutation [13]. Many of patients were resistance to multiple drug classes and many of these mutations elaborate resistancy to other drugs in the same class.…”
Section: Discussionsupporting
confidence: 90%
“…Individuals with M184V mutation are subjected to high resistance to FTC and 3TC, which are the common medications of each first-line regimen. M184I/V mutation was the most frequent mutation (31.6%) among NRTI-based regimens; similar findings were observed in studies from Iran [10, 12] and other regions in which the common mutation for NRTIs was M184V, with an estimated prevalence of 40 and 88.5%, respectively [13]. 3TC and FTC M184V mutation creates a significant decrease in viral replication capacity.…”
Section: Discussionsupporting
confidence: 80%
“…For the purpose of quality control, the sequences were analyzed in recall and all the analyses were performed in accordance with the Stanford University’s HIV Drug Resistance Database Program (http://hivdb.stanford.edu) [10, 11]. We comprised all drug resistance mutations that presented low-, intermediate-, or high-level resistance.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of the M184V mutation in the current study was the most common one among other studies carried out on the NRTI class [13,14,16]. M184V mutation is related to high resistance to lamivudine and emtricitabine [17]: lamivudine has been prescribed in the Iranian ART regimen and high-level drug resistance to emtricitabine can be attributed to cross-resistance.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, a single mutation is often sufficient to cause resistance to the currently recommended first generation of NNRTIs, nevirapine, or efavirenz [18,19,20]. Inconsistent with the study, K103N was reported more commonly than in previous studies [16]. Resistance mutation to PI was not observed in the ART-experienced group, but previous studies determined that the most common protease inhibitor mutation was L90M [13].…”
Section: Discussionmentioning
confidence: 97%